Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Review - Page 904: 5


$(f\circ g)(x)=x^2+2x-1$

Work Step by Step

Functions involved: $f(x)=x^2-2$ $g(x)=x+1$ Substitute $g(x)$ into $f(x)$: $(f\circ g)(x)=(x+1)^2-2$ Expand: $(f\circ g)(x)=x^2+2x+1-2$ Simplify: $(f\circ g)(x)=x^2+2x-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.